2020
DOI: 10.1093/applin/amaa034
|View full text |Cite
|
Sign up to set email alerts
|

Words Go Together Like ‘Bread and Butter’: The Rapid, Automatic Acquisition of Lexical Patterns

Abstract: While it is possible to express the same meaning in different ways (‘bread and butter’ versus ‘butter and bread’), we tend to say things in the same way. As much as half of spoken discourse is made up of formulaic language or linguistic patterns. Despite its prevalence, little is known about how the processing system treats novel patterns and how rapidly a sensitivity to them arises in natural contexts. To address this, we monitored native English speakers’ eye movements when reading short stories containing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(52 citation statements)
references
References 41 publications
4
46
2
Order By: Relevance
“…The inclusion of existing binomials allowed us to determine whether repeated exposures influence performance for novel binomials, such that they begin to behave like existing binomials. The nine existing and 24 novel (invented) binomials were taken from a study by Conklin and Carrol (2020) on adult L1 speaker acquisition of lexical (word order) patterns. Existing binomials were all 'noun and noun', were highly frequent, and had a highly conventionalized order (forward form 'son and daughter' significantly greater than reversed form 'daughter and son', t(11) = 9.23, p < .001).…”
Section: Binomials and Passagesmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of existing binomials allowed us to determine whether repeated exposures influence performance for novel binomials, such that they begin to behave like existing binomials. The nine existing and 24 novel (invented) binomials were taken from a study by Conklin and Carrol (2020) on adult L1 speaker acquisition of lexical (word order) patterns. Existing binomials were all 'noun and noun', were highly frequent, and had a highly conventionalized order (forward form 'son and daughter' significantly greater than reversed form 'daughter and son', t(11) = 9.23, p < .001).…”
Section: Binomials and Passagesmentioning
confidence: 99%
“…Based on this, 11 occurrences in the BNC seemed to be a reasonable upper limit for novel items. It is important to note that the items did not exist in English as formulaic items (which was established in Conklin & Carrol, 2020). A native speaker of Arabic judged that the novel items were not formulaic in Arabic.…”
Section: Binomials and Passagesmentioning
confidence: 99%
See 1 more Smart Citation
“…As they emphasize, the influence of the frequency of the binomial as a unit supports the usage-based claim that multi-word units are retained in memory. Conklin and Carrol ( 2020 ) found converging results with newly-introduced binomials; reading times decreased as exposure increased, while reading time to the reversed order decreased as exposure increased. Similarly, the most frequently occurring cases tend to be more fixed in their order than less frequent cases (Cooper and Ross, 1975 ; Gustafsson, 1976 ; Mollin, 2013 ; Morgan and Levy, 2015 ).…”
Section: Cognitive Accessibilitymentioning
confidence: 94%
“…As discussed below, these factors include frequency, definiteness, and priming, as well as semantic animacy, relevance to the speaker, prototypicality, and concreteness (Cooper and Ross, 1975 ; Benor and Levy, 2006 ; Onishi et al, 2008 ; Lohmann and Takada, 2014 ; Morgan and Levy, 2016 ; Tachihara and Goldberg, 2021 ). As additionally reviewed below, a good deal of work has also demonstrated that prior experience with one order or the other predicts future uses (Cooper and Ross, 1975 ; Mollin, 2013 ; Morgan and Levy, 2015 ; Conklin and Carrol, 2020 ). Yet neither of these factors on its own predicts a change in word order, because the meanings of the terms has hardly changed, and previous male-first word order failed to persist across diachronic time.…”
Section: Introductionmentioning
confidence: 99%